Mediating Role of Attitude on Halal Awareness, Religiosity, Product Knowledge, COO on Purchase Intention Korean Food - Marchia , Ai Dike; Asih, Daru (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Purpose – This paper seeks to examines the Korean Wave or Hallyu phenomenon (South Korean food products) and identifies factors that influence purchase intention, mediated by attitude, halal awareness, religiosity, halal product knowledge, and country of origin among Muslims in Jakarta. Methodology/approach – This research is quantitative in nature with a research sample consisting of 160 respondents. Data were collected through a questionnaire with a Likert scale of 1-5, then analyzed using the Structural Equation Model (SEM) with the help of Smart PLS software. Findings – It The results of the research obtained by halal awareness have a significant positive effect on attitudes and purchase intention, attitudes have a significant positive effect in mediating the effect of halal awareness on purchase intention. Religiosity has a significant positive effect on attitude and purchase intention, attitude has a significant positive effect in mediating the effect of Religiosity on purchase intention. Knowledge of halal products has a significant positive effect on attitudes and purchase intention, attitudes have a significant positive effect in mediating the effect of knowledge of halal products on purchase intention. Halal awareness has a significant positive effect on attitudes and purchase intention, attitudes have a significant positive effect in mediating the effect of halal awareness on purchase intention. Attitude has a significant positive effect on purchase intention.